Rancang Bangun Sistem Informasi Perhitungan Angka Kredit Dosen STMIK STIKOM Indonesia - Brigida Arie Minartiningtyas; I Ketut Adi Sumariata (SINTECH (Science and Information Technology) Journal, 2018)
Operational Guidance Assessment of Credit Score Increase / Rank Academic Lecturer issued by Directorate General of Higher Education Ministry of Education and Culture Year 2014 indicates that each lecturer is entitled to propose the proposed increase in functional positions with the calculation of credit numbers, not exception for lecturer fixed foundation at Private Higher Education. STMIK STIKOM Indonesia is one of the private universities that still use a manual system to perform data processing for lecturers who will propose promotion and positions of lecturers. The number of elements or criteria and different values in each element in the assessment of credit numbers cause lecturers have difficulty in calculation and obtain information about the functional level of the positions, therefore required a computer application that can assist in the process of calculation quickly, precisely and accurately so it can be made a reference before proposing a functional promotion. From the test results that have been done can be seen that the system built has been able to run well. All system functionality goes in line with expectations